(untitled) (Bangladesh Journal of Agricultural Research, 2008)
In an experiment, six levels of benzyl adenine (0.2.5, 5.0, 7.5, 10.0, 12.5 and 15.0 mg/I) in combination with three levels of (CCC) chloro choline chloride (0,125, 250 and 500 mg/I) were evaluated against control treatment (0) in each case to find out their optimum levels for microtuberization in potato variety Diarnant. Microtuberization was the earliest by 13 days at 10 mg/I BA. The number and average weight of microtuber per flask vas increased with increasing rate of BA and reached maximum of 12.9 and 252.1 mg respectively at 10 mg/I BA and decreased onwards with further increase of BA concentration. The increase rate of CCC increased the number of microtuber but decreased average weight. The maximum number and average weight of microtuber were recorded at 500 mg/I CCC and in absence of CCC respectively. Key Words: BA, CCC, potato, microtuber. doi:10.3329/bjar.v33i3.1601 Bangladesh J. Agril. Res. 33(3) : 419-425, September 2008